The Pd (II) Reduction Mechanisms in Bacillus megaterium Y-4 Revealed by Proteomic Analysis - Yuan Chen; Jiaxing Wang; Daidi Chen; Boxi Wang; Jinchuan Wu; Rongrong Liu; Qingxin Li (Nanomaterials, 2024)
Many studies have been conducted on the microbial reduction of Pd (II) to palladium nanoparticles (Pd-NPs) due to the environmental friendliness, low cost, and the decreased toxicity of Pd (II) ions. In this study, we investigate the reduction mechanism of Pd (II) by Bacillus megaterium Y-4 through proteomics. The data are available via ProteomeXchange with identifier PXD049711. Our results revealed that B. megaterium Y-4 may use the endogenous electron donor (NAD(P)H) generated by nirB, tdh, and fabG and reductase to reduce Pd (II) to Pd-NPs. The expression levels of fabG, tdh, gudB, and rocG that generate NAD(P)H were further increased, and the number of reduced Pd-NPs was further increased with the exogenous electron donor sodium formate. Endogenous electron mediators such as quinones and flavins in B. megaterium Y-4 can further enhance Pd (II) reduction. The findings provided invaluable information regarding the reduction mechanism of Pd (II) by B. megaterium Y-4 at the proteome level.